Rancang bangun sistem informasi manajemen proyek pt.inti (simpronti) berbasis website dengan metode weighted product - Haryati Haryati; Nunu Nugraha Purnawan; Hilda Nur Febriliani; Nurfitria Khoirunnisa; Dwi Vernanda (Journal of Information System, Applied, Management, Accounting and Research, 2022)
Project management Information System with Weighted Product method is a system that is built to manage projects in PT. INTI system with the ability to become assessment media experts to assess a project, choosing a project holder with Weighted Product method produces recommendations as well as monitoring and also evaluation on the project to be executed. The purpose of this project management information system is to improve the system of evaluation and monitoring of projects that are still manual, so that with the system is expected work process can be more convenient for data storage to switch into the database. This project management information system is created by referring to the method of SDLC (System Development Life Cycle) with waterfall model that has several steps in sequence from analysis to system maintenance. Systems built in the form of applications with Web-based.